Indication and short term outcome of Mechanical Ventilation in Neonates in a tertiary care hospital - Jahan, Nasim; Haque, Zabrul SM; Mannan, Md Abdul; Nasrin, Mahmuda; Afroz, Farhana; Parvez, Anwar; Rahman, Taifur; Islam, Manjurul (Bangladesh Journal of Medical Science, 2017)
Background: Mechanical ventilation of newborn has been practiced for several years with advances in many ways. As compared to the western world, neonatal ventilation in our country started in recent years. Subjects, Methods and Results: A retrospective chart review was conducted to analyze the common indications and outcome of neonates requiring mechanical ventilation in neonatal intensive care unit at Ad-Din Medical College Hospital from January 2012 to July 2013. Fifty eight neonates were ventilated over a period of 19 months of whom 39 (67.24%) survived. Respiratory distress syndrome was the commonest indication for ventilation (32.75%), followed by Perinatal asphyxia (18.96%), Pneumonia (13.79%), Neonatal Sepsis (13.79%), Meconium aspiration syndrome 6(10.16%) & Pneumothorax 6 (10.16%). Among the babies who survived, 35(89.74%) were managed solely with conventional ventilator and 4 babies required both conventional and High Frequency Oscillatory (HFOV) ventilation. Survival rate was higher where birth weight >2500gm (76.19%) and gestational age 34-37 weeks (88.88%). Survival rates was (69.23%) in <30 weeks and 60% in <1000 g. Prolong ventilator support was needed for Respiratory Distress Syndrome without surfactant (mean 254 hrs), Perinatal asphyxia (mean 187hrs) and Neonatal sepsis (mean 187hrs). Common complications were Pneumonia (12.06%), Pneumothorax (10.34%), sepsis (8.6%) & Pulmonary hemorrhage (3.4%). Survival rate was higher in babies requiring mechanical ventilation for respiratory distress syndrome (84.21%). Conclusion: Use of surfactant could decrease the duration of ventilation and mortality further in babies with respiratory distress syndrome. Bangladesh Journal of Medical Science Vol.16(1) 2017 p.24-28